Greenhouse Manufacturers and Suppliers - George J. Hochmuth; Robert C. Hochmuth (EDIS)
This document contains a partial list of greenhouse manufactures and suppliers. The list is intended for use as a reference only and mention of a company is not an endorsement of that company or their products. This document is HS1020, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date October 2005.